2020
DOI: 10.1038/s41467-020-17047-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a novel human adeno-associated virus capsid with neurotropic properties

Abstract: Recombinant adeno-associated viruses (rAAVs) are currently considered the safest and most reliable gene delivery vehicles for human gene therapy. Three serotype capsids, AAV1, AAV2, and AAV9, have been approved for commercial use in patients, but they may not be suitable for all therapeutic contexts. Here, we describe a novel capsid identified in a human clinical sample by high-throughput, long-read sequencing. The capsid, which we have named AAVv66, shares high sequence similarity with AAV2. We demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Indeed, most AAV capsids are not known to efficiently transduce oligodendrocytes (Burger et al, 2004 ; Cearley and Wolfe, 2006 ; Cearley et al, 2008 ; San Sebastian et al, 2013 ). This fact has prompted studies evaluating the use of oligodendrocyte-specific promoters to drive expression in oligodendrocytes (Chen et al, 1998 ; Lawlor et al, 2009 ) as well as the pursuit of novel recombinant capsids with significant oligodendrocyte tropism as demonstrated in rodents (Powell et al, 2016 ), and the characterization of oligodendrocyte tropism in a novel naturally occurring AAV capsid (Hsu et al, 2020 ). Taken together, these study results indicate that AAV vector research continues to yield important advances toward achieving both safety and efficacy for in vivo gene therapy approaches to leukodystrophies.…”
Section: Gene Transfer Therapy: Considerations In Leukodystrophiesmentioning
confidence: 99%
“…Indeed, most AAV capsids are not known to efficiently transduce oligodendrocytes (Burger et al, 2004 ; Cearley and Wolfe, 2006 ; Cearley et al, 2008 ; San Sebastian et al, 2013 ). This fact has prompted studies evaluating the use of oligodendrocyte-specific promoters to drive expression in oligodendrocytes (Chen et al, 1998 ; Lawlor et al, 2009 ) as well as the pursuit of novel recombinant capsids with significant oligodendrocyte tropism as demonstrated in rodents (Powell et al, 2016 ), and the characterization of oligodendrocyte tropism in a novel naturally occurring AAV capsid (Hsu et al, 2020 ). Taken together, these study results indicate that AAV vector research continues to yield important advances toward achieving both safety and efficacy for in vivo gene therapy approaches to leukodystrophies.…”
Section: Gene Transfer Therapy: Considerations In Leukodystrophiesmentioning
confidence: 99%
“…This may be due to overall differences in amino acid composition, resulting in varying capsid surface charge profile and overall structural characteristics of different AAV serotypes. 30,31 As a proof-of-concept study, commercially available or in-house produced samples or mixtures corresponding to five different AAV serotypes (AAV1, AAV2, AAV3, AAV8, and AAV9) were selected. When analyzed by AEX-HPLC using linear separation gradient of 0%-50% buffer B, all samples from different serotypes showed two distinct peaks with considerable overlap as seen with AAV6 (Figure S2).…”
Section: Extension Of the Empty-full Hplc Assay To Other Serotypesmentioning
confidence: 99%
“…In the past few years, brain-derived neurotrophic factor (BDNF), glial cell line derived neurotrophic factor (GDNF), insulin-like growth factor 1 (IGF-1), vascular endothelial growth factor (VEGF), Neuregulin 1 and Neurturin were used to treat ALS under pre-clinical settings [92,[96][97][98]. Different studies showed that AAV mediated expression of these neurotrophic factors delayed disease onset and prolonged survival in SOD1 mice model [96][97][98][99][100][101][102].…”
Section: Tests Of Gene Therapy Strategies To Treat Both Familial and mentioning
confidence: 99%
“…Overall, the increasing number of pre-clinical studies in non-human primates (NHP) and the generation of novel AAV vectors, more efficient in targeting CNS cells [ 87 ], will help assessing the best method for gene therapy delivery to ALS patients. Several other parameters will have to be considered to move forward the field, such as the long-term transgene expression, which produces sustained expression of silencing molecules.…”
Section: Aav-mediated Silencing Approaches For Fals (Sod1 and C9orf72mentioning
confidence: 99%